2021
DOI: 10.3389/fgene.2021.705284
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH3 Variants and Genotype-Phenotype Features in Chinese CADASIL Patients

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a cerebral small vessel disease caused by mutations in the NOTCH3 gene. Archetypal disease-causing mutations are cysteine-affecting variants within the 34 epidermal growth factor-like repeat (EGFr) region of the Notch3 extracellular subunit. Cysteine-sparing variants and variants outside the EGFr coding region associated with CADASIL phenotype have been reported. However, the linkage between untypical varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 39 publications
1
28
1
Order By: Relevance
“…Although other studies have shown EGFRs 7-34 variants to be associated with very mild phenotype, [24][25][26][27][28] EGFRs 18-34 variants appeared to be as severe as EGFRs 1-9 with respect to stroke in our study. However, there were fewer patients with variants in EGFRs 18-34 which reduces confidence in this comparison.…”
Section: Discussioncontrasting
confidence: 99%
“…Although other studies have shown EGFRs 7-34 variants to be associated with very mild phenotype, [24][25][26][27][28] EGFRs 18-34 variants appeared to be as severe as EGFRs 1-9 with respect to stroke in our study. However, there were fewer patients with variants in EGFRs 18-34 which reduces confidence in this comparison.…”
Section: Discussioncontrasting
confidence: 99%
“…14,15 Previous work has pointed out that the proportion of migraine with aura was 20%-40% in Caucasian while in Chinese patients it was often around or lower than 20%. 7,[16][17][18][19] Our results showed that the proportion in Caucasian was over 50%, which meant the difference between Asians and Caucasians might bigger than we know. Also, work from Taiwan pointed out that less frequent temporal pole involvement was associated with p.Arg544Cys.…”
Section: Clinical Features Of Cadasil Patients In Different Populationsmentioning
confidence: 60%
“…This is reflected at the neuroanatomical level, as patients with pathogenic variants in EGFR domains 1-6 showed more severe white matter hyperintensity on brain MRI and an earlier onset of stroke than those with mutations in EGFR domains 7-34 [1]. In addition, patients carrying cysteine-affecting variants reported to show more severe clinical severity than those carrying cysteine-sparing variants [7,8]. Patients with the cystine-sparing p.Arg75Pro mutation showed a significantly lower stroke frequency and white matter hyperintensity than patients with p.Arg141Cys or p.Arg182Cys, although all three such mutations were located in EGFR domains 1-6 [7].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the genotype-phenotype correlation, the determinants of clinical severity in CADASIL remain unknown [1,[6][7][8]. However, several factors seem to be associated with clinical severity, including the location of the mutation, whether the variant affects cysteine residues, as well as other cardiovascular risk factors [1,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation